Womanism, Literature, and the Transformation of the Black Community, 1965-1980 - Eaton, Kalenda C. (Short Guides to Business Risk, 2008)
This book examines how cultural and ideological reactions to activism in the post-Civil Rights Black community were depicted in fiction written by Black women writers, 1965-1980. By recognizing and often challenging prevailing cultural paradigms within the post-Civil Rights era, writers such as Toni Morrison, Alice Walker, Toni Cade Bambara, and Paule Marshall fictionalized the black community in critical ways that called for further examination of progressive activism after the much publicized 'end' of the Civil Rights Movement. Through their writings, the authors' confronted marked shifts within African American literature, politics and culture that proved detrimental to the collective 'wellness' of the community at large.